Biodegradable coating agent composition for thermal bonding and preparation method thereof
By using biodegradable coating agent compositions with components such as thermoplastic starch and natural resins in the thermal bonding material, the problem of the inability to biodegrade existing materials and the viscosity of starch-based materials has been solved, and the effect of high bond strength and environmental protection is achieved.
Patent Information
- Application Number
- CN202311757073.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-17
- Filing Date
- 2023-12-20
- Publication Date
- 2025-04-18
AI Technical Summary
The existing thermal bonding materials cannot be biodegradable and have problems of unenvironmental protection. At the same time, the viscosity of starch-based materials increases after gelatinization, resulting in difficulty in circulation.
The viscosity and bond strength are adjusted by a specific preparation method using a coating agent composition for biodegradable thermal bonding, including thermoplastic starch, pH adjuster, viscosity stabilizer, a first solvent, a second solvent and a natural resin.
The coating agent composition that achieves biodegradability, environmental protection and high bond strength is suitable for various substrates, and has a stable viscosity, which is suitable for thermal bonding production processes.
Smart Images

Figure CN119842319A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a biodegradable thermal adhesive coating composition and a preparation method thereof, and more specifically, to a biodegradable thermal adhesive coating composition and a preparation method thereof, which is environmentally friendly due to its biodegradability, has excellent adhesion to various substrates such as paper and plastic, and has stable water resistance and viscosity changes, and is suitable for thermal bonding production processes.
[0002] The biodegradable thermal adhesive composition of the present invention does not require an adhesive and a laminating device, and thus can reduce production costs and reduce environmental impact, and can be used in various fields. Background Art
[0003] In today's society, various ready-to-eat foods or disposable packaged foods are becoming widely popular, and as a result, food packaging materials are also widely used. These food packaging materials need to meet the following conditions: they must have appropriate barrier properties to moisture and air to maintain the freshness and taste of the food, and they must have excellent adhesion to the substrate. At the same time, in view of environmental and health issues, they must be environmentally friendly and suitable for the human body. In addition, in addition to food packaging materials, various packaging materials such as pharmaceutical packaging materials and infusion bags are also required to have water resistance, barrier properties, biodegradability, and environmental protection. However, existing packaging materials use PE, PP plastics and other films as thermal bonding materials by laminating. Such packaging materials are not biodegradable, so there is a problem of being environmentally unfriendly.
[0004] Among the starch-based materials developed as alternative materials, although they are excellent in recyclability and environmental protection, the following problem has been pointed out: after starch gelatinization, the hydrogen bonds between starch chains increase over time, causing the viscosity of the reactants to increase, making them unable to circulate.
[0005] Therefore, there is a need for a composition that is applicable to various substrates such as paper, metal, glass, plastic, etc., is environmentally friendly, harmless to the human body, and has stable thermal adhesiveness, water resistance and viscosity. Summary of the invention
[0006] Problems to be solved by the invention
[0007] In order to solve the problems of the prior art as described above, the present invention aims to provide a biodegradable thermal adhesive coating composition having excellent physical properties and a method for preparing the same. In particular, the present invention aims to provide a biodegradable thermal adhesive coating composition and a method for preparing the same, which can be applied to various substrates and will not age over time, thereby achieving a stable viscosity and maintaining a certain adhesive strength.
[0008] Methods used to solve problems
[0009] In order to achieve the above object, the present invention provides a biodegradable thermal adhesive coating composition, which includes thermoplastic starch (TPS), a pH adjuster, a viscosity stabilizer, a first solvent, a second solvent and a natural resin.
[0010] In addition, the present invention relates to a method for preparing a biodegradable thermal adhesive coating composition, which comprises the following steps:
[0011] a) adding a pH adjuster to the first solvent;
[0012] b) adding thermoplastic starch to the solution of a);
[0013] c) heating the solution of b);
[0014] d) adding a viscosity stabilizer to the heated solution of c) to carry out a reaction;
[0015] e) cooling the solution of d);
[0016] f) adding a second solvent to the cooled solution;
[0017] g) adding a natural resin to the solution of f); and
[0018] h) After stirring the solution in g), recovering the final solution.
[0019] Effects of the Invention
[0020] The biodegradable thermal adhesive coating composition of the present invention has the following advantages: excellent thermal adhesive strength, excellent durability, adjustable viscosity, and can be applied to various substrates such as paper and plastic. Therefore, it is expected that it can improve the utilization rate not only as a food packaging material, but also as a packaging material in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a photograph showing the liquid phase stability of the composition of Example 1.
[0022] Figure 2 (a) is the composition of Comparative Example 1, Figure 2 (b) is a photograph showing the liquid phase stability of Comparative Example 2.
[0023] Figure 3 This is a photograph showing the liquid phase stability of Comparative Example 3.
[0024] Figure 4 (a) is a photograph showing the water absorption of the composition of Example 1. Figure 4(b) is a photograph showing the water absorption of the composition of Comparative Example 11.
[0025] Figure 5 This is a photograph showing the result of thermally bonding the composition of Example 4 and then peeling off the coated paper. DETAILED DESCRIPTION
[0026] The present invention will be described in more detail below through specific examples. The following example describes a preferred specific example of the present invention, and it should be understood that the scope of the present invention is not limited to the matters described in the following example.
[0027] In the present invention, "%" means % by weight.
[0028] "Biodegradable" generally refers to a substance that breaks down through the action of naturally occurring microorganisms such as bacteria, fungi, algae, heat, moisture, or other environmental factors.
[0029] "Thermoplastic starch" refers to starch obtained by treating starch with a plasticizer.
[0030] The invention relates to a biodegradable thermal adhesive coating composition, which comprises thermoplastic starch (TPS), a pH regulator, a viscosity stabilizer, a first solvent, a second solvent and a natural resin.
[0031] In one aspect, the composition is a composition consisting of 7 to 25 wt % of thermoplastic starch (TPS, Thermo Plastic Starch), 1 to 5 wt % of a pH adjuster, 0.08 to 1.0 wt % of a viscosity stabilizer, 3 to 20 wt % of a second solvent, 3 to 35 wt % of a natural resin, and the remainder of the first solvent.
[0032] In one aspect, the thermoplastic starch is added at 7 to 25 wt % of the coating composition. When the range is met, there is a favorable effect in achieving thermal bonding strength and production efficiency. When the content of the thermoplastic starch is less than 7 wt %, the amount of solvent becomes relatively large and it takes a longer time to dry the solvent in the process, which is disadvantageous from the perspective of production efficiency. When it is greater than 25 wt %, the viscosity becomes very high, so it is difficult to use in the coating process.
[0033] In the present invention, acrylic resin, silane hydrolyzate, urethane resin, polyolefin resin and biodegradable resin can be mixed or combined with the starch to give the starch adhesion and coating stability. The biodegradable resin can include at least one of PLA (polylactic acid), PCL (polycaprolactone), PPC (polypropylene carbonate), PGA (polyglycolic acid), PBAT (polybutylene adipate terephthalate), PBS (polybutylene succinate), PHA (polyhydroxyalkanoate), TPS (thermoplastic starch) and PEC (polyethylene carbonate). A hard biodegradable resin (such as PLA) and a soft biodegradable resin (such as PCL, PPC) can be combined to prepare various coating materials, and the coating materials can be used to form biodegradable films with various physical properties. For example, by mixing a hard biodegradable resin and a soft biodegradable resin in a solution, a biodegradable film with excellent physical properties such as barrier properties, coating properties, and mechanical strength can be formed. In addition, paper coated with the biodegradable film can be used for various purposes and is environmentally friendly.
[0034] The pH regulator has the function of promoting the gelatinization of starch and inhibiting aging. As long as it is an alkaline substance, it is not particularly limited and any known material can be selected. In one aspect, the pH regulator can be any one selected from the inorganic alkaline compounds, namely, sodium hydroxide, potassium hydroxide, calcium hydroxide, and sodium carbonate. In addition, the organic base compound includes primary amine, secondary amine, tertiary amine or a mixture thereof, wherein the primary amine is any one or more selected from the group consisting of methylamine, methanolamine, ethylamine, ethylamine, ethylamine, ethylamine, propylamine, 3-amino-1-propanol, isopropylamine, monoisopropanolamine, tert-butylamine, butylamine, hexylamine, dodecylamine, cyclohexylamine, ethylenamine and hexamethylenediamine, and the secondary amine is any one or more selected from the group consisting of dimethylamine, diethylamine, diethanolamine, dipropylamine, N-ethylen ...propylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, dipropylamine, dipropylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, dipropylamine, dipropylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethylamine, diethyl any one or more of the group consisting of: lmethylamine (N-ethylmethylamine), N-Methylpropylamine (N-methylpropylamine), 3-(METHYLAMINO)-1-PROPANOL (3-(methylamino)-1-propanol), N-Isopropylmethylamine (N-isopropylmethylamine), Dibutylamine (dibutylamine), Di-sec-butylamine (di-sec-butylamine), Dioctylamine (dioctylamine), N-methylcyclohexylamine (N-methylcyclohexylamine), Pyrrolidine (pyrrolidine), Pyridine (pyridine) and Diethylenetriamine (diethylenetriamine), wherein the tertiary amine is selected from the group consisting of Trimethylamine (trimethylamine), Trimethanolamine (trimethylolamine), Triethylamine (triethylamine), Triethanolamine (triethanolamine), Dimethylethanolamine (dimethylethanolamine), N,N-Dimethylpropylamine (N,N-dimethylpropylamine), N,Any one or more of the group consisting of N-Dimethylbutylamine(N,N-dimethylbutylamine), 3-Dimethylamino-1-propanol(3-dimethylamino-1-propanol), N,N-Dimethyldodecylamine(N,N-dimethyldodecylamine), N,N-Dimethyloctadecylamine(N,N-dimethyloctadecylamine), Tripentylamine(tripentylamine), N,N-Dimethylcyclohexylamine(N,N-dimethylcyclohexylamine), 3-(Dimethylamino)benzylalcohol(3-(dimethylamino)benzylalcohol and N,N,N′,N′-Tetramethyl-1,4-butanediamine(N,N,N',N'-tetramethyl-1,4-butanediamine),
[0035] In particular, sodium hydroxide can be used. In one aspect, the pH regulator can be used in a range of 1 to 5 wt%. When the added amount is less than 1 wt%, the gelatinization of starch is not obvious and its anti-aging effect is reduced. When it is greater than 5 wt%, the coating agent contains excessive hydrophilic substances, thereby reducing the water resistance of the coated film.
[0036] Viscosity stabilizers are large single molecules located within the starch chain. They prevent hydrogen bonding between starch chains to suppress the viscosity increase and can adjust the required viscosity according to the type. In addition, due to the high carbon number and small number of functional groups, they are also conducive to improving water resistance.
[0037] In one aspect, the viscosity stabilizer can be any one or more selected from the group consisting of lecithin, lysolecithin, glycerin fatty acid ester, sucrose fatty acid ester, propylene glycol fatty acid ester, whey protein isolate (9410WPI), whey protein concentrate (8000WPC), soy protein isolate (SPI), rice protein isolate (RPI), oat protein isolate (OPI), pea protein isolate (PPI), casein, sodium caseinate, corn zein, gelatin, gluten, dextrins, carrageenans, Tween 80, Tween 20 and cellulose. In one aspect, the viscosity stabilizer can be used in an amount ranging from 0.08 to 1.0% by weight. When the added amount is less than 0.08 wt %, there is no effect of preventing the viscosity from increasing, and when it is greater than 1.0 wt %, there is a problem of reduced thermal adhesiveness. On the one hand, it is preferably used in the range of 0.1 to 0.5 wt %.
[0038] The first solvent is not limited, and may be, for example, any one or more of water, distilled water, and purified water.
[0039] The second solvent can use an alcohol having a carbon number of 1 to 6, for example, it can be one or more selected from the group consisting of alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, sec-pentanol, tert-pentanol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, cyclohexanol and mixtures thereof.
[0040] The second solvent can improve coating properties and the speed of producing coated paper, and can also play a role in preventing corrosion by enzyme inhibition when using materials of natural substrates.
[0041] On the one hand, the second solvent is used at 3 to 20 weight %. When the addition amount is less than 3 weight %, there is no effect of improving coating properties and production efficiency, and when it is greater than 20 weight %, starch may be precipitated. On the one hand, preferably 3 to 10 weight %.
[0042] On the one hand, the composition of the present invention may further include natural resins, preferably, shellac may be further added. Shellac is a kind of animal resin, which is manufactured by purifying or bleaching the yellow mucus secreted by lac bugs, and is generally used as a coating or finishing material. In the present invention, it is used as a coating agent for the purpose of improving water resistance and antibacterial properties. On the one hand, shellac is used in an amount of 3 to 35 weight %. When the addition amount is less than 3 weight %, there is no effect of improving water resistance and antibacterial properties. When it is greater than 35 weight %, it may react abnormally with starch and precipitate in a state of starch and shellac agglomeration, thereby being difficult to use as a coating agent. On the one hand, it is preferably 15 to 30 weight %.
[0043] In addition to the above ingredients, other additives may be added to the composition of the present invention, for example, dispersing aids, melt stabilizers, processing stabilizers, heat stabilizers, light stabilizers, antioxidants, heat aging stabilizers, brighteners, anti-blocking agents, adhesives, lubricants, water-soluble polymers and fillers. Dispersing aids can be used, for example, for the following purposes: to help form a uniform dispersion, delay or prevent component separation. Similarly, dispersing aids can improve the water dispersibility of the coating composition.
[0044] In addition, the present invention provides a method for preparing a biodegradable thermal adhesive coating composition, which comprises the following steps: a) adding a pH adjuster to a first solvent; b) adding thermoplastic starch to the solution of a); c) heating the solution of b); d) adding a viscosity stabilizer to the heated solution of c) to react; e) cooling the solution of d); f) adding a second solvent to the cooled solution; g) adding a natural resin to the solution of f); and h) stirring the solution of g) and recovering the final solution.
[0045] In the step a), a pH adjuster may be added to the first solvent while stirring with a mechanical stirrer. Then, thermoplastic starch may be added in the step b), and the reactants may be heated to 60 to 90° C. in the step c), but the present invention is not limited thereto.
[0046] Then, in step d), a viscosity stabilizer may be added to the reaction solution while slowly stirring to carry out the reaction. The viscosity stabilizer may be added in the content range of the types described in detail above. Thereafter, the reaction may be carried out for 1 to 4 hours, but is not limited thereto.
[0047] In step e), the reaction solution may be cooled to room temperature.
[0048] In step f), the second solvent is slowly added to the cooled solution while stirring, and then in step g), the natural resin is added to the solution. Then, in step h), the solution of g) is stirred and the final solution is recovered. The reaction may be performed for 10 to 30 minutes, but is not limited thereto.
[0049] In one aspect, the natural resin is shellac.
[0050] In one aspect, the prepared biodegradable thermal adhesive coating composition can be further dispersed using ultrasonic waves, a high-pressure disperser or a homogenizer so as to be uniformly dispersed. Preferably, a high-pressure dispersion method can be used for dispersion.
[0051] In one aspect, further heating and / or pressurizing processes may be performed to adjust physical properties, and a drying process may be performed to remove residual solvent.
[0052] The biodegradable thermal adhesive coating composition can be provided on the substrate in a thickness of 0.1 μm to 90 μm. The thicker the thickness, the higher the thermal adhesive strength, and the thinner the thickness, the more economical the manufacturing process.
[0053] The substrate of the coating composition for biodegradable heat adhesive is not limited, and can be paper, plastic or metal, etc., and a functional layer for imparting additional physical properties can be included between the substrate and the coating layer. For example, a primer layer or an oxygen barrier layer can be selectively stacked, or a primer layer and an oxygen barrier layer can be stacked simultaneously. The following steps may be further included: the primer layer or the oxygen barrier layer is applied with a thickness of 1 μm to 10 μm. Regarding primer, for example, when a coating liquid is applied on a film coated with (surface treated) a carbamate primer, adhesion is improved, so that the coating layer coated on the substrate film is not easy to peel off. In addition, in order to improve adhesion, surface treatments such as plasma or corona can also be further performed on the film.
[0054] In one aspect, the step of providing the biodegradable thermal adhesive coating composition on the substrate can be performed by coating the biodegradable thermal adhesive coating composition on the substrate. For example, spray coating, spin coating, dip coating, gravure coating, micro gravure coating, comma coating, knife coating, direct coating, bar coating, etc. can be used, but not limited thereto.
[0055] The solvent of the composition applied on the substrate may be evaporated. Although not limited, hot air drying may be performed using a hot air dryer at a temperature of 60 to 150° C. for 1 to 5 minutes, preferably at 100° C. for 2 to 3 minutes.
[0056] Hereinafter, the following examples are examples of the present invention, and these examples do not limit the scope of the present invention.
[0057] [Example 1]
[0058] 88.4 g (68 wt%) of distilled water as the first solvent was stirred at 300 rpm using a mechanical stirrer, and 1.5 g (1.15 wt%) of 1N NaOH was added. Then, 10 g (7.69 wt%) of thermoplastic starch was added and the reactant was heated to 80°C. When it reached 80°C, it was stirred at 500 rpm, and 0.1 g (0.08 wt%) of lecithin was slowly added, and the mixture was reacted at 80°C for 1 hour and then cooled. 100 g of the reactant at room temperature was stirred at 1000 rpm using a mechanical stirrer, and 10 g (7.69 wt%) of ethanol as the second solvent was slowly added. Ethanol was added, and 20 g (15.38 wt%) of shellac was added after 10 minutes, and the mixture was stirred for 20 minutes, and the reactant was then recovered. The final composition was uniformly dispersed using a high-pressure disperser (1000 bar, 3 passes) to achieve a particle size of about 100 nm.
[0059] [Example 2 to Example 25]
[0060] A coating composition was prepared by the same process as in Example 1 except that the components and contents described in Table 1 below were different.
[0061] [Comparative Examples 1 to 11]
[0062] Coating agent compositions were prepared by the same process as in Example 1 except that the components and contents were set to the compositions of Comparative Examples 1 to 11 in Table 1.
[0063]
Table 1
[0064]
[0065] [Comparative Example 12]
[0066] The same process as in Example 1 was used to prepare the composition except that the high pressure dispersion process was not performed after the composition was recovered.
[0067] [Experimental Example 1]
[0068] Measuring Liquid Phase Stability
[0069] After the compositions of the examples and comparative examples were stored at normal temperature and humidity for 30 days, their stability was observed with the naked eye. Figure 1 This is a photograph showing the liquid phase stability of the composition of Example 1. Figure 2 (a) and (b) are photographs showing the liquid phase stability of the compositions of Comparative Examples 1 and 2, respectively. Figure 3 This is a photograph showing the liquid phase stability of the composition of Comparative Example 12 which was not subjected to the dispersion process.
[0070] The composition of Example 1 remained uniform and stable, while the compositions of Comparative Examples 1 and 2 were corroded or gelled, respectively, and were difficult to be used as coating compositions. Comparative Example 12 showed a thickening phenomenon, and was therefore not suitable as a coating composition.
[0071] [Experimental Example 2]
[0072] Measuring viscosity
[0073] The viscosity of the compositions prepared according to the examples and comparative examples was measured using a viscometer (Brookfield, DV2TRV) at room temperature and humidity (20±5°C, 55±5%) (spindle: No. 06, rpm: 100 rpm). The results are shown in Table 2.
[0074] [Experimental Example 3]
[0075] Measuring water absorption
[0076] After the base paper is placed on a glass plate, about 1 to 2.5 g of the coating composition prepared according to the embodiment and the comparative example is dropped on the base paper, and the composition is coated on the base paper with a certain thickness using a bar coater. The film coated with the composition is dried at 100° C. for 2 minutes using a hot air dryer to produce coated paper. For the produced coated paper, the Cobb test method (TAPPI T441) is used to pour distilled water into 100 cm 2 The test piece was placed on a circular test piece for 60 seconds, and then the weight after the test was calculated - the weight before the test to evaluate the water absorption. The results are shown in Table 2. Figure 4 (a) is a photograph showing the water absorption of the composition of Example 1. Figure 4 (b) is a photograph showing the water absorption of the composition of Comparative Example 1. It was confirmed that the composition of Example 1 was stable without visible changes, while the composition of Comparative Example 1 absorbed water and caused the paper to soak.
[0077] [Experimental Example 4]
[0078] Measuring thermal bond strength
[0079] For the coating agent prepared according to the above-mentioned Experimental Example 3, a thermal gradient tester (Qmesys, QM930D) was used. After the lower plate of the heating plate was set to 60°C and the upper plate was set to 150°C, two coated papers were placed between the plates in a manner that the coating layers of the two coated papers were face to face, and pressure was applied for 1 second to perform thermal bonding. After that, the thermally bonded coated paper was cut into a length of 10 mm and a width of 100 mm (the thermal bonding area was 10 mm in length and 25 mm in width) to prepare a test piece, and then the bonding strength was measured by a universal material testing machine (Lloyd, LS1). The results are shown in Table 2.
[0080]
Table 2
[0081]
[0082] As shown in Table 2, in the case of the compositions of the examples, effective physical properties as adhesive compositions were generally exhibited, while the compositions of the comparative examples could not be used due to corrosion or gelation. It was generally evaluated that the compositions of Examples 5 to 8, 10, 13, 14, 20, 22 to 25 were preferred in terms of viscosity, water absorption and adhesive strength. The viscosity of Example 6 increased slightly, the drying degree of Example 8 was slightly slow, the water absorption of Example 11 was high, abnormal phenomena occurred in Examples 15 and 19, and the thermal adhesive strength of Example 21 was low.
[0083] In Experimental Example 3, the coated paper to which the composition of Example 1 was applied was further thermally bonded and then peeled off. The results are as follows: Figure 5 It was confirmed that the paper was torn when peeled off and the sealing property was very excellent.
Claims
1. A biodegradable thermal adhesive coating composition, wherein: The biodegradable thermal adhesive coating composition comprises thermoplastic starch (TPS), a pH adjuster, a viscosity stabilizer, a first solvent, a second solvent and a natural resin.
2. The composition according to claim 1, wherein The composition consists of 7 to 25 wt % of thermoplastic starch, 1 to 5 wt % of a pH adjuster, 0.08 to 1 wt % of a viscosity stabilizer, 3 to 20 wt % of a second solvent, 3 to 35 wt % of a natural resin and the remainder of the first solvent.
3. The composition according to claim 2, wherein The natural resin is shellac.
4. The composition according to claim 1, wherein The pH adjuster is at least one selected from sodium hydroxide, potassium hydroxide, triethylamine, ethylenediamine, and dimethylethanolamine (DMEA).
5. The composition according to claim 1, wherein The viscosity stabilizer is selected from the group consisting of lecithin, lysolecithin, glycerol fatty acid ester, sucrose fatty acid ester, propylene glycol fatty acid ester, whey protein isolate (9410WPI), whey protein concentrate (8000WPC), soy protein isolate (SPI), rice protein isolate (RPI), oat protein isolate (OPI), pea protein isolate (PPI), casein, sodium caseinate, corn zein, gelatin, gluten, dextrins, carrageenans, Tween 80, Tween 20 and cellulose.
6. The composition according to claim 1, wherein The first solvent is any one or more of water, distilled water, and purified water.
7. The composition according to claim 1, wherein The second solvent is one or more selected from the group consisting of ethanol, methanol, isopropanol and a mixture thereof.
8. A packaging material, wherein: The packaging material is formed from the composition according to any one of claims 1 to 7.
9. A method for preparing a biodegradable thermal adhesive coating composition, wherein: The preparation method comprises the following steps: a) adding a pH adjuster to the first solvent; b) adding thermoplastic starch to the solution of a); c) heating the solution of b); d) adding a viscosity stabilizer to the heated solution of c) to carry out a reaction; e) cooling the solution of d); f) adding a second solvent to the cooled solution; g) adding a natural resin to the solution of f); and h) After stirring the solution in g), recovering the final solution.
10. The preparation method according to claim 9, wherein: The natural resin is shellac.
11. The preparation method according to claim 9, wherein: In the step c), the temperature is raised to a range of 60 to 90°C.
12. The preparation method according to claim 9, wherein: In the step d), the reaction is carried out within a range of 1 to 4 hours after the viscosity stabilizer is added.
13. The preparation method according to claim 10, wherein: After the shellac is added, the reaction is carried out while stirring for 10 to 30 minutes.
14. The preparation method according to claim 9, wherein: After the step g), a step of dispersing the recovered composition by performing a high-pressure dispersion step is further added.
Citation Information
Patent Citations
Enhanced adhesion and sealing between two fibrous materials
CN116601357A
Water-resistant starch composition and foam thereof
JP2000319630A
Water dispersion coating for molded article of foodbowl using biodegradable resin and coating methodthereof
KR1020050000749A
Biodegradable polymeric material, biodegradable products and methods of manufacture and use therefor
US20220275201A1
Biodegradable polymeric mixtures based on thermoplastic starch
US6235815B1